2006
DOI: 10.1186/1471-2407-6-177
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in PIK3CAare infrequent in neuroblastoma

Abstract: Background: Neuroblastoma is a frequently lethal pediatric cancer in which MYCN genomic amplification is highly correlated with aggressive disease. Deregulated MYC genes require cooperative lesions to foster tumourigenesis and both direct and indirect evidence support activated Ras signaling for this purpose in many cancers. Yet Ras genes and Braf, while often activated in cancer cells, are infrequent targets for activation in neuroblastoma. Recently, the Ras effector PIK3CA was shown to be activated in divers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 36 publications
(41 reference statements)
0
21
0
Order By: Relevance
“…Gain of function of the a subunit is common in human cancers by overexpression or mutations . In our NB tumour material, we could not identify any mutations in the PIK3CA gene (data not shown) and Dam et al (2006) have reported only infrequent mutations in their NB material. The PI3 kinases are generally considered to function as oncogenes.…”
Section: Discussionmentioning
confidence: 59%
“…Gain of function of the a subunit is common in human cancers by overexpression or mutations . In our NB tumour material, we could not identify any mutations in the PIK3CA gene (data not shown) and Dam et al (2006) have reported only infrequent mutations in their NB material. The PI3 kinases are generally considered to function as oncogenes.…”
Section: Discussionmentioning
confidence: 59%
“…Therefore, the effect on kinase activity of these mutations is unknown. (24) We did not identify any PIK3CA mutations in our larger set of NB cases.…”
Section: Discussionmentioning
confidence: 72%
“…16). PI3K signaling is not generally hyperactivated by PTEN or PIK3CA deletions or mutations in neuroblastoma (29,30), and, as shown in Supplementary Fig. S2A, PTEN protein was expressed in all the neuroblastoma cell lines studied.…”
Section: Pi3k Differentially Regulates Hif1a and Hif2a Protein Expresmentioning
confidence: 73%